2020
DOI: 10.1002/csr.1960
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofCSRand environmental triggers on employee green behavior: The mediating effect of employeewell‐being

Abstract: This article explores the influence of corporate social responsibility (CSR) and three green triggers of environment (awareness, concern, and knowledge) on employee well‐being and green behavior. The study engages the stimulus–organism–response model for testing the association between CSR and well‐being of employees that leads to employee green behavior. Furthermore, social exchange theory has been utilized to describe the association between well‐being and green behavior of employees. Data have been gathered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
173
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(198 citation statements)
references
References 107 publications
(127 reference statements)
21
173
1
3
Order By: Relevance
“…The study argued that the extant literature is under-explored in establishing the dimensional relationship of CSR activities with consumer loyalty. There have been studies in prior literature on the topic of CSR, however, the majority of these studies investigated the phenomenon of CSR in a related organizational context-for example, financial performance [45,76] or the employees' related outcomes [77,78], whereas the potential impact of CSR from the perspective of consumer-related outcomes is something that is largely ignored in the extant literature.…”
Section: Discussionmentioning
confidence: 99%
“…The study argued that the extant literature is under-explored in establishing the dimensional relationship of CSR activities with consumer loyalty. There have been studies in prior literature on the topic of CSR, however, the majority of these studies investigated the phenomenon of CSR in a related organizational context-for example, financial performance [45,76] or the employees' related outcomes [77,78], whereas the potential impact of CSR from the perspective of consumer-related outcomes is something that is largely ignored in the extant literature.…”
Section: Discussionmentioning
confidence: 99%
“…The scale for employee well-being was adapted from Ahmed, Zehou [ 69 ], which also measured the responses on a 7-point Likert scale (1 = strongly disagree and 7 = strongly agree). The detailed information about all items of the questionnaire is presenting in Appendix A .…”
Section: Methodsmentioning
confidence: 99%
“…A study of EGB among employees in China examined whether EGB can be predicted by green human resource management (green HRM) through the information need of employees (Zhang et al, 2019). Another study among hotel employees in Pakistan showed that EGB was affected by CSR, environmental awareness, environmental concern, and environmental knowledge through the sense of well-being (Ahmed et al, 2020).…”
Section: Need For the Studymentioning
confidence: 99%